Analyze the quality Magnesium – aluminium binary alloy concerning its flowability, tensile strength and hardness with various types of moulds - Mohamad Sohaifol Soid (Universiti Malaysia Perlis, 2008)
This final year project is based on analyze the quality of magnesium – aluminium alloy products concerning of its flowability, tensile strength and hardness with various types of moulds. The mentioned method of molds is silica sand molding, river sand molding and CO2. molding . Based on the different types on molding its bring to the different on mechanical properties for each of the sample. These mechanical properties are obtained by series of test mention above which is flowability test, tensile strength test and hardness test. From this series of test, its mechanical properties can be identified and one conclusion can be made. To strengthen this project analysis, series of test are added which are chemical composition analysis and microstructure or metallographic analysis. All the testing conducted are using mold magnesium – aluminum samples (Dog Bone Pattern) and all testing involve the used of Universal Testing Machine (UTM) for tensile strength test, Microhardness Vickers machine for hardness test, X-ray Fluorescence analyzer for chemical composition analysis and Light Transmitted Microscope for microstructure analysis. Conclusions made through this project are hundred percent based on the result and discussion made.